The Evaluation of Gamma Knife Indices for Treatment Planning (Single Session, Multi-Session, and Hypofractionation) for Gamma Knife Radiosurgery in Patients with Meningioma (Iraqi Journal of Medical Sciences, 2025)
Background:    Meningiomas are the most common benign intracranial tumors, making up about one-third of all primary brain tumors, some can cause issues due to difficult removal in sensitive or hard-to-reach areas. Gamma knife radiosurgery (GKR) is an effective treatment for meningioma.Objective:    To assess better planned treatments, such as multisession and hypofractionation, as well as single session stereotactic radiosurgery.Methods:    Fifty-two patients with meningiomas, diagnosed by neurosurgeons or oncologists, participated in a cross-sectional study at Saad Alwitry Hospital’s Gamma Knife Center. Gamma Knife therapy was administered by a specialist, with computed tomography (CT) and magnetic resonance imaging (MRI) used to evaluate the tumor characteristics. The dosimetry parameters used in this study are coverage, selectivity, gradient index (GI), and time (minutes). These parameters are obtained for each plan session.Results:    There were significant differences in the mean value of selectivity between the three groups, with the highest value among the patients who received multi-session doses of GKR (Gy) than those who received single and hypo sessions of GKR (Gy). The results also revealed non-significant and slight differences in the mean values of the GI between patients who received multi, single, and hypo sessions. Patients who received multiple sessions required fewer mean values of GKR shot numbers. This study also found that patients who received hypo-session GKR required less time (minutes) for gamma knife radiation therapy. Ultimately, the results showed the differences in tumor size (cm3) before and after GKR treatment according to doses given in the three sessions.Conclusion:    Multisession GKR therapy offers a low-morbidity alternative that is secure, efficient, and well tolerated for these large lesions. The meningioma multisession GKR is successful in reducing the size of large tumors.Keywords:    Gamma knife, stereotactic radiosurgery, coverage, selectivity, gradient index (GI), number of Shots (dose), tumor Reduction.Citation:    Ibrahim RT, Ahmed RS, Hassan YM. The evaluation of gamma knife indices for treatment planning (single session, multi-session, and hypofractionation) for gamma knife radiosurgery in patients with meningioma. Iraqi JMS. 2025; 23(1): 139-146. doi: 10.22578/IJMS.23.1.16